1996
DOI: 10.1161/01.cir.94.9.2241
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Nitrate Tolerance Is Not Associated With Reduced Bioconversion of Nitroglycerin to Nitric Oxide

Abstract: The results suggest that vascular and hemodynamic NTG tolerance occurs despite high and similar rates of NO formation by NTG in tolerant and nontolerant target tissues. This finding is compatible with the assumption that reduced biological activity of NO, rather than reduced bioconversion of NTG to NO, contributes to in vivo development of nitrate tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 18 publications
2
26
0
2
Order By: Relevance
“…We have demonstrated in this study that capacity of GTNtolerant aortas to produce NO from 100 mol/L GTN was not different from control aortas. These results are consistent with a previous study 66 and argue against the idea of decreased bioconversion of GTN into NO in GTN-tolerant vessels. These results also do not support a role for NO in GTNinduced vasodilatation.…”
Section: Gtn/no In Blood Vesselssupporting
confidence: 92%
“…We have demonstrated in this study that capacity of GTNtolerant aortas to produce NO from 100 mol/L GTN was not different from control aortas. These results are consistent with a previous study 66 and argue against the idea of decreased bioconversion of GTN into NO in GTN-tolerant vessels. These results also do not support a role for NO in GTNinduced vasodilatation.…”
Section: Gtn/no In Blood Vesselssupporting
confidence: 92%
“…However, it has been shown that even during nitrate tolerance caused by long-term GTN administration, the bioconversion of GTN to NO may remain unaltered. 20 Given the subtle nature of the impairment in NMD observed in the present study, it is unlikely that this defect would significantly influence the measurement of FMD. Our present results demonstrate a close relationship between NMD and FMD, but causality of this association cannot be proven in this cross-sectional study setting, and it is possible that the correlation is merely a result of colinearity attributable to similar risk factor influences on these measures of arterial function.…”
mentioning
confidence: 71%
“…1 A-D) is compatible with reports that rabbit (34)(35)(36) and rat (37) organs differ in their capacity to generate NO from GTN. These spin-trapping studies indicate that NO formation during acute GTN infusion (34,35,37) or more prolonged transdermal administration (36) is greatest in kidney, liver, and lung, less in heart and vena cava, and marginal in aorta and RBCs. Our data show that, during GTN biotransformation, heart and liver also are major nitros(yl)ation sites, especially compared with vascular tissue.…”
Section: Discussionmentioning
confidence: 92%